2009
DOI: 10.1210/me.2009-0055
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression ofAd4BP/SF-1in Fetal Adrenal Progenitor Cells Leads to Ectopic Adrenal Formation

Abstract: Deficiency of adrenal 4 binding protein/steroidogenic factor 1 (Ad4BP/SF-1; NR5A1) impairs adrenal development in a dose-dependent manner, whereas overexpression of Ad4BP/SF-1 is associated with adrenocortical tumorigenesis. Despite its essential roles in adrenal development, the mechanism(s) by which Ad4BP/SF-1 regulates this process remain incompletely understood. We previously identified a fetal adrenal enhancer (FAdE) that stimulates Ad4BP/SF-1 expression in the fetal adrenal gland by a two-step mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…Disruption of the Ftz-F1 gene in mice, which encodes for Ad4BP/SF-1, results in both absence of adrenal glands and gonads [18]. In contrast, recent transgenic mice experiments demonstrated that Ad4BP/SF-1 overexpression results in gonadal tissue remaining adjacent to the kidneys [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the Ftz-F1 gene in mice, which encodes for Ad4BP/SF-1, results in both absence of adrenal glands and gonads [18]. In contrast, recent transgenic mice experiments demonstrated that Ad4BP/SF-1 overexpression results in gonadal tissue remaining adjacent to the kidneys [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies by Zubair, et al provided significant insights into the relationship between the FZ and the DZ/adult cortex 26, 27, 59, 60 . Using the FAdE-Cre mouse model, these investigators observed proliferating cells in a scattered pattern throughout the adrenal gland until E13.5 13, 60 .…”
Section: Fetal and Early Adult Development Of The Adrenal Cortexmentioning
confidence: 99%
“…Modulation of SF-1 dosage is also relevant for the mechanism of adrenal development impairment induced by the lack of CITED2, a transcriptional cofactor supposedly interacting with WT1 (Val et al 2007). On the other hand, transgenic overexpression of SF-1 in mice under the control of its own FAdE led to increased adrenal size and to the formation of ectopic adrenal tissue in the thorax (Zubair et al 2009). All together, these data evidence the importance of SF-1 dosage for both adrenal and gonadal development.…”
Section: Dosage At the Core Of Sf-1 Biological Activitymentioning
confidence: 99%